2004
DOI: 10.1080/13691830410001699603
|View full text |Cite
|
Sign up to set email alerts
|

Older Irish migrants living in London: identity, loss and return

Abstract: More than a quarter of a million people left Ireland for Britain in the 1940s and 1950s.The literature on the Irish experience in Britain reveals high levels of social deprivation and poor health, some of which has been attributed to prejudice and discrimination, the legacy of a colonial relationship. Other commentators have suggested the more interwoven complexities for Irish migrants in Britain of maintaining an authentic identity. In this paper we explore the myth of return, encompassing notions of identity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 19 publications
1
45
0
Order By: Relevance
“…The literature on the Irish experience in Britain has revealed that most individuals migrated for economic reasons, although this generally co-existed with a 'pull' factor of desire to escape or change (Gmelch 1986(Gmelch , 1987Ryan 2004;Leavey et al 2004). …”
Section: Historical Overview Of Irish Migrationmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature on the Irish experience in Britain has revealed that most individuals migrated for economic reasons, although this generally co-existed with a 'pull' factor of desire to escape or change (Gmelch 1986(Gmelch , 1987Ryan 2004;Leavey et al 2004). …”
Section: Historical Overview Of Irish Migrationmentioning
confidence: 99%
“…These findings are explained, at least to some extent, in terms of higher social adversity, migrant stress, social isolation, depression, loneliness and poor living conditions of the migrant populations. Focusing on the experiences of Irish migrants living in Britain in the second half of the twentieth century, the sociological literature has revealed high levels of social deprivation and poor health for Irish migrants, especially for men (Leavey et al 2004;Commander et al 1999;Harrison and Carr-Hill 1992;Mullen et al 1996;Pearson et al 1991;Cochrane and Bal 1989;Nazroo 1997). …”
Section: Psychic Costs Of (Return) Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…While it may be stretching a point to argue that the mass emigration of the 1950s had an equally traumatic effect on the collective Irish psyche, it is still an embedded memory that is invoked. Arguably exacerbating the traumatic effect is the collective memory not just of the hardships experienced by 1950s migrants in Britain, but also the hardships inflicted by life in 1950s Ireland, and the subsequent legacy of resentment and betrayal at the necessity of leaving (Leavey et al, 2004).…”
Section: Migration Collective Memory and The 1950smentioning
confidence: 99%
“…Peterson-Veatch 1999), or both ethnicity and migration (as in e.g. Leavey et al 2004), as will be discussed below.…”
Section: Ethnicity Migration or Both With An Interest In Old(er) Agementioning
confidence: 99%